HUBUNGAN PENGETAHUAN DAN SIKAP BIDAN TERHADAP PELAKSANAAN INISIASI MENYUSUI DINIHUBUNGAN PENGETAHUAN DAN SIKAP BIDAN DENGAN PELAKSANAAN INISIASI MENYUSU DINI DI PMB WILAYAH KECAMATAN MEDAN TUNTUNGAN TAHUN 2021 - Dwi Ris Hasanah; Emelia Apriani Tampubolon; Kristiova Masnita Saragih (Jurnal Kebidanan, 2022)
Early Initiation of Breastfeeding (IMD) is the process of a baby suckling immediately after birth, in which the baby is allowed to find the mother's nipple on its own (not thrust into the nipple). Breastfeeding properly and correctly can increase the success of exclusive breastfeeding, the coverage of breastfeeding is to prevent infant mortality, impaired infant development, and prevent hypothermia. The IMD process creates closeness between mother and baby. This study aims to determine the relationship between knowledge and attitudes of midwives on the implementation of Early Breastfeeding Initiation (IMD). The research method used was analytic observational with a cross sectional approach, with a sample of 34 midwives who opened their own practice around Medan Tuntungan District. The results of the analysis showed that of the 34 respondents who had sufficient knowledge as many as 18 people (53%) and the majority carried out IMD as many as 12 people (66.7%). And of the 34 respondents the majority had a negative attitude as many as 27 people (79.5%), and the majority did not carry out IMD as many as 17 people (47%). There is a significant relationship between the knowledge and attitudes of midwives towards the implementation of the IMD, where the better the knowledge, the more motivated the midwife to implement the IMD. With a value of = 0.015. And a negative attitude will cause the midwife not to carry out the IMD with a value of = 0.021. It is hoped that the midwives at BPM, Medan Tuntungan Sub-district in 2021, will further improve the IMD implementation program in the future.